2017
DOI: 10.5958/2394-8159.2017.00005.6
|View full text |Cite
|
Sign up to set email alerts
|

Marketing Channels, Marketing Cost, Margin and Producer's Share in Consumer's Rupee in Paddy Marketing

Abstract: The marketing of paddy covers a vast spectrum of activities including all the functions and processes involved in the movement of the produce from the point of production to the point of consumption. The district Etah, Uttar Pradesh was selected purposively for the research work. Four market channels were selected for the study of marketing channels, marketing costs, margins and producer's share in consumer's rupee with the help of available data and information. In Channel-I, the producer had paid ` 16 per qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Market margin is the price gap between the price paid by consumer and the amount received by the producers (Khanal et al, 2020). Similarly, producer's share is the fractional part of the consumer's payment received by the farmers (Kumar et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Market margin is the price gap between the price paid by consumer and the amount received by the producers (Khanal et al, 2020). Similarly, producer's share is the fractional part of the consumer's payment received by the farmers (Kumar et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Gross income obtained in small size group was 36073 followed by 35000 in medium and 38900 minimum in large size group. The lead functional form was the cobb Douglas log function which produced R 2 of 0.93,0.94 and 0.94in marginal, small and medium farm group [8,9]. MVP value of various input used in wheat crop grown in Kothawan block revealed that in case of wheat, only manure and fertilizer showed MVP less than unit which means that these resources were overused, so their use should be reduced.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Market margin can be defined as the price gap between the consumer's paid amount and the amount received by the farmers (Bowbrick 1976). Likewise, producer's share is the fraction of the consumer's payment received by the producers (Kumar et al 2017). The study reveals that the marketing margin and Producer's share of cucumber was NRs.…”
Section: Marketing Channelsmentioning
confidence: 99%